Structure and organization of full-length epidermal growth factor receptor in extracellular vesicles by cryo-electron tomography - Monica Gonzalez-Magaldi; Anuradha Gullapalli; Ophelia Papoulas; Chang Liu; Adelaide Y.-H. Leung; Luqiang Guo; Axel F. Brilot; Edward M. Marcotte; Zunlong Ke; Daniel J. Leahy (Proceedings of the National Academy of Sciences, 2025)
We report here transport of full-length epidermal growth factor receptor (EGFR), Insulin Receptor, 7-pass transmembrane receptor Smoothened, and 13-pass Sodium-iodide symporter to extracellular vesicles (EVs) for structural and functional studies. Mass spectrometry confirmed the transported proteins are the most abundant in EV membranes, and the presence of many receptor-interacting proteins in EVs demonstrates their utility for characterizing membrane protein interactomes. Cryo-electron tomography of EGFR-containing EVs reveals that EGFR forms clusters in both the presence and absence of EGF with a ~3 nm gap between the inner membrane and cytoplasmic density. EGFR extracellular region (ECR) dimers do not form regular arrays in these clusters. Subtomogram averaging of the 150 kDa EGF-bound EGFR ECR dimer yielded a 15 Å map into which the crystal structure of the ligand-bound EGFR ECR dimer fits well. These findings refine our understanding of EGFR activation, clustering, and signaling and establish EVs as a versatile platform for structural and functional characterization of human membrane proteins in cell-derived membranes.